Avaliação da via aérea faringiana com uso de dispositivo de avanço mandibular em pacientes com apnéia obstrutiva do sono : análise dos resultados por exames de imagem e polissonografia - Woltmann, Marcus (2014)
Purpose: The pharyngeal airway may change after mandibular advancement in patient using intraoral device in obstructive sleep apnea (OSA) treatment. The aim of this study was to evaluate the dimensional and volumetric changes of superior airway promoted by an adjustable mandibular advancement device (AMAD) and the polysomnographic results in patients with OSA facial pattern facial Cl II. Materials and Methods: The present prospective study selected 11 patients with OSA (5 males and 6 females) and radiographs and ct scans, and polysomnographic exam were performed with and without the use of AMAD. The airway was assessed in the following aspects: superior pharyngeal space (S1), posterior palatal space (S2), median pharyngeal space (S3), posterior pharyngeal space (S4), inferior pharyngeal space (S5), pharyngeal volume (CT1), anterior-posterior lengths of the smallest cross-sectional area (CT2), lateral lengths of smallest cross-sectional area (CT3), pharyngeal smallest cross-section area (CT4). The analyzed variables of the polysomnographic data were: AH total (total number of apnea and hypopnea), AHI (apnea and hypopnea index - calculated as the average number of respiratory events per hour of sleep); AI (Apnea index), HI (Hypopnea index), Apnea duration, Hypopnea duration, Lowest O2% saturation. Results: The use of the AMAD induced an insignificant decrease of the pharyngeal airway as observed in the S1 (20.091 to 20.01mm decrease of -0,26%) and S4 (11.08 to 10.59mm decrease of -4.2%). A not statistically significant increase was observed in S2 (8.33 to 9.43mm increase of 13.67%), S3 (18.23 to 18.34mm increase of 1,2%) and CT1 (13393 to 15948 mm3 increase of 19,07%). Statistically significant increases were observed in S5 (11.92 to 15.67mm increase of 47.08%), CT2 (media of 5.81 to 7,71mm increase of 32,7%), CT3 (17,3 mm to 22,33 mm increase of 29.07%) and CT4 (79,77 to 119,38 mm2 increase of 49.65%), and determined a significant decrease of the variables total AH (159,9 to 54,8 reduction of 34,27%), AHI (21,57 to 7,54 decrease of 34.95%) and AI (17,33 to 3,99 reduction 23,1%). A nonsignificant reduction in the duration of apnea (16,4 to 14,7 reduction of 10.36%), Hypopnea (18.42 to 16,94 reduction of 8.03%). A nonsignificant increase of HI (3.26 to 3.29 increase of 0.92%), Lowest O2% saturation (76.6 to 82.9 increase of 8.22%). Conclusions: A correlation between the mandibular advancement and changes in the measurements of pharyngeal airway were significant with the use of AMAD in the inferior pharyngeal space (S5), anterior posterior lengths of smallest pharyngeal cross-sectional area (CT2), lateral lengths of smallest pharyngeal cross-sectional area (CT3), and pharyngeal smallest cross-section area (CT4), and polysomnographic data showed a significant improvement with the reduction of the variables AH total, AHI, HI. Results showed that the use of the AMAD allows an increase of the superior airway and improves important variables of the polysomnography exam, being the lateral teleradiography, CT scan and polysomnography are effective methods for the diagnosis and evaluation of the treatment s progress.